1983
DOI: 10.1002/pssa.2210770125
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Effects in N+-Implanted LiNbO3

Abstract: A model of damage formation in LiNbO3 by N+ (150 keV, 300 K)‐implantation is discussed including the results of RBS, volume expansion, and refractive index investigation of simultaneously implanted, X‐, Y‐ and Z‐cuts. For dose values D italicN + ≦ 1 × 1015 cm−2 most of the displaced Nb atoms occupy vacant octahedral lattice sites. Because of the high stability of the crystal structure in the c‐direction, a complete amorphization of the implanted LiNbO3 layers is not attained even with D italicN + = 4 × 1016cm−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…2(b)). This confirms the assumption that the different defect concentration measured by RBS channeling is a consequence of the preferential arrangement of displaced Nb-atoms on vacant octahedral sites [7,16]. Due to their position in the lithium niobate lattice these sites cause different dechanneling of the analyzing He-ions along different crystal axis.…”
Section: Methodssupporting
confidence: 84%
“…2(b)). This confirms the assumption that the different defect concentration measured by RBS channeling is a consequence of the preferential arrangement of displaced Nb-atoms on vacant octahedral sites [7,16]. Due to their position in the lithium niobate lattice these sites cause different dechanneling of the analyzing He-ions along different crystal axis.…”
Section: Methodssupporting
confidence: 84%
“…As a result of annealing at T, = 670 K the refractive index changes are reduced by nearly a factor of one half. The differences in the absolute values and in the profile of refractive index between the ordinary and extraordinary cases shown also here shall not be discussed because this has been done in our previous paper [ 7 ] . We want to concentrate our consideration on the influence of absorption.…”
Section: Absorption and Reflection Coefficientsmentioning
confidence: 93%
“…For irradiation, already the first systematic studies on ion implantation in LN by Jetschke et al [99] and Götz and Karge [100,101] showed a clear anisotropy in the generation of lattice defects. For irradiation with 150 keV N + ions at room temperature amorphization at the surface was reached with fluences of 5 × 10 15 cm −2 and 2 × 10 16 cm −2 for x-and y-cut material.…”
Section: Nuclear Damage Dominated Casesmentioning
confidence: 99%